Dizziness – Causes, Symptoms, Diagnosis and Treatment - Woźniak, Oskar; Wąsik , Joanna; Gryboś , Kacper; Sepioło , Weronika; Kiełbratowska , Julia; Mikulska, Jowita Mikulska; Lewandowski , Mikołaj; Kurkiewicz , Wojciech (Journal of Education, Health and Sport, 2025)
Dizziness is a common symptom affecting 15-35% of people, often leading them to seek medical help. It can arise from various causes, including neurological, otolaryngological, metabolic, cardiological, and psychological factors, and is often mistaken for fainting or weakness. Dizziness may be short-lived or chronic, and accurately identifying its cause is crucial for effective treatment. It is categorized into peripheral and central vertigo, based on the origin of the problem.Dizziness is described variably, from spinning sensations (vertigo) to feelings of unsteadiness or lightheadedness. It may be accompanied by nausea, vomiting, and other symptoms depending on the underlying condition. A thorough medical history, neurological examination, vestibular tests, imaging, and hearing tests are key steps in diagnosing the cause of dizziness. Treatment depends on the identified cause and includes medication, vestibular rehabilitation and surgical treatment.